ANALISIS KESALAHAN SISWA DALAM MEMECAHKAN MASALAH PISA DITINJAU DARI GENDER - Nurjannah Nurjannah; Mirna Nurlili; Andi Auliya Ismuna (Journal on Mathematics Education Research (J-MER), 2021)
This research was qualitative research with a descriptive approach that aims to describe the results of the analysis of student errors based on Polya's stages in solving PISA problems in terms of gender. This research was carried out in SMP Negeri 2 Kahu, in class VIII female and male students who had relatively similar mathematical abilities. Data collection is done by giving mathematical problem-solving tasks in the form of PISA questions and interviews. To test the credibility of the data, time triangulation was performed. At different times the tasks and interviews are given with problems that are equivalent to the previous tasks.In the stage of understanding the problem and making a plan of resolution, the female subject did not make mistakes because she was able to identify the problem by determining the keywords of the problem at hand but the subject could not fully understand the purpose of the problem because the subject did not know what concepts were related to the problem. At the stage of implementing the plan, the calculation results obtained by the subject are wrong. This happens because the subject is not able to understand and relate the concepts by the problem being faced so that the calculation results are wrong. This has an impact on the stage of re-checking, the subject examines and checks the steps and the results of calculations that are done repeatedly to ensure that the calculation results are correct even though the answer is still wrong because the concept used to solve the PISA problem is wrong.In the stage of understanding the problem and making a plan of the resolution, the subject does not make a mistake because it identifies the problem by determining the keywords of the problem encountered after reading the problem. Then gather information / mathematical facts related to the problem that will be used to solve the problem. At the stage of making a solution plan, the subject made a mistake by making a problem-solving plan without using the correct concepts. Or in other words, the subject is only guessing what concepts are appropriate for solving the problem. At the stage of implementing the plan, the subject carries out the chosen strategy. However, because the plan is chosen was not based on a strong concept, the results of the problem solving obtained were wrong. In the re-checking stage, the subject checks by examining and re-checking step by step the problem-solving strategies that are used and all are appropriate. However, because the strategy chosen was only guessed, the subjects did not know that the answers obtained were wrong.